CLIFF-GRADS Science Collaboration Series 2020 - Final Session and Future Collaboration - Leahy, Sinead; Chirinda, Ngonidzashe; Sander, Björn Ole; Arango, Jacobo; Tomlin, Hazelle; Montgomery, Hayden (Global Research Alliance on Agricultural Greenhouse Gases (GRA) & CGIAR Research Program on Climate Change Agriculture and Food Security (CCAFS), 2020)
Featured Speakers: Dr. Sinead Leahy, Senior Scientist, New Zealand Agricultural Greenhouse Gas Research Centre (NZAGRC); Dr. Ngonidzashe Chirinda, Soil and Climate Change Scientist, Mohammed VI Polytechnic University, Morocco; Dr. Bjoern Ole Sander, Senior Scientist and Climate Change Specialist, International Rice Research Institute; Dr. Jacobo Arango, Environmental Biologist at the Tropical Forages Program at CIAT.